2002
DOI: 10.1080/02652030110085377
|View full text |Cite
|
Sign up to set email alerts
|

Lead content in Spanish market infant formulas and toxicological contribution

Abstract: Lead content was investigated in infant formulas by using graphite furnace atomic absorption spectroscopy (GFAAS). Formulas were distinguished as 'beginner', 'continuation' and 'special infant formula', the latter being classified as subtypes 'hypoallergenic', 'without lactose', 'vegetable base' and 'others'. The mean concentrations of lead were 25.7+/-8.4, 36.9+/-6.4 and 43.5+/-16.3 microg kg(-1) for beginner, continuation and special infant formula, respectively. Two-factor (types and subtypes) variance anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 7 publications
1
7
0
Order By: Relevance
“…The range of lead determined agrees reasonably well with most literature values (Ikem et al 2002, Moreno-Rojas 2002, Tripathi et al 1999, Rodríguez et al 1999, Biego et al 1998, Krachler et al 1998, Ursinyova and Hladikova 1997, Esteve et al 1994, Dabeka 1989, Dabeka and Mckenzie 1987,1988.…”
Section: Resultssupporting
confidence: 77%
“…The range of lead determined agrees reasonably well with most literature values (Ikem et al 2002, Moreno-Rojas 2002, Tripathi et al 1999, Rodríguez et al 1999, Biego et al 1998, Krachler et al 1998, Ursinyova and Hladikova 1997, Esteve et al 1994, Dabeka 1989, Dabeka and Mckenzie 1987,1988.…”
Section: Resultssupporting
confidence: 77%
“…Whereas sample calcination at temperatures above 400°C has been used by some authors [10,21,54,[104][105][106] (Table 1) several studies have shown that it may not be the most appropriate method since significant losses of As, Hg, Cd and Pb can occur [105]. In general, ashing methods may present poorer accuracy and provide lower analyte recovery when compared with acid digestion methods [54,104].…”
Section: Ashingmentioning
confidence: 96%
“…To improve this shortcoming, transversally heated atomizers (THA) were designed which provided a more uniform distribution of temperature over the length of the tube, decreasing the rate of atom loss by condensation, thereby increasing sensitivity and decreasing the detection limits. In spite of this, several studies reporting the determination of Cd, Cu and Pb in biological samples in the last 10 years have been conducted with ETAAS spectrometers equipped with LHAs [2,6,10,13,23,30,33,54,69,70,75,77,78,85,[87][88][89]106,121,123,137]. The most recent have been based on measurements with improved equipment (Zeeman background correction systems, multielement determination system) conducted with THAs [28,36,38,40,41,47,58,61,[79][80][81]90,92,94,98,114,115,125,127,128,131,134,[147]…”
Section: Spectrometer Improvementsmentioning
confidence: 98%
See 2 more Smart Citations